1991
DOI: 10.1101/gad.5.7.1224
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cDNAs encoding the polypyrimidine tract-binding protein.

Abstract: The polypyrimidine tract of mammalian introns is recognized by a 62-kD protein (pPTB). Mutations in the polypyrimidine tract that reduce the binding of pPTB also reduce the efficiency of formation of the pre-spliceosome complex containing U2 snRNP. The PTB protein was purified to homogeneity by affinity chromatography on a matrix containing poly(U), and peptide sequence was used to isolate several cDNAs. Because a variety of cell types express mRNA complementary to these cDNAs, PTB may be a ubiquitous splicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
226
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(239 citation statements)
references
References 72 publications
13
226
0
Order By: Relevance
“…Our finding of PTB in HFFs, G 0 HFFs, hTERT-HFFs and hTERT-RPEs was consistent with its widespread expression in multiple cell types (Gil et al, 1991). Intriguingly, the induction of PTB was preceded by the appearance of smaller PTB isoforms, which reacted with a monoclonal antibody against the PTB carboxy terminus.…”
Section: Discussionsupporting
confidence: 63%
“…Our finding of PTB in HFFs, G 0 HFFs, hTERT-HFFs and hTERT-RPEs was consistent with its widespread expression in multiple cell types (Gil et al, 1991). Intriguingly, the induction of PTB was preceded by the appearance of smaller PTB isoforms, which reacted with a monoclonal antibody against the PTB carboxy terminus.…”
Section: Discussionsupporting
confidence: 63%
“…The fact that PTB may be just one component of a larger complex is indicated by our finding that complex I is at least 150-kDa in size (K. Singh and L. R. Covey, unpublished data) and the presence of a different, but related complex that binds the E5Ј-HaeIII transcript. PTB is expressed ubiquitously and as three alternatively spliced isoforms in many different cells and tissue types (46,48). We have previously shown that complex I only forms in T cells after extended activation.…”
Section: Discussionmentioning
confidence: 99%
“…Several isoforms and paralogs of PTB have been reported [10,40,41]. Brain-specific PTB is known to be a different gene product of PTB, i.e., a paralog of PTB.…”
Section: Ptb In Drm Fraction Of Replicon Cells Consists Of Multiple Imentioning
confidence: 99%